Privilege and Oppression: The Configuration of Race, Gender, and Class in Southern Ontario Auto Plants, 1939 to 1949 - Sugiman, Pamela (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2001)
Abstract In most studies of the automotive industry in Canada, the workforce has been constructed as uniformly white and male. However, a tiny number of Black men have long had a presence in the industry, occupying the dirtiest, most hazardous, and least desirable jobs in the auto foundries of St. Catharines and Windsor, Ontario. This paper attempts to reconstruct the working lives and union involvements of mese men. The paper highlights the themes of racialization and gendering within the sphere of capitalist production. In examining multiple oppressions, simultaneously experienced and resisted, the study furthermore demonstrates the ways in which relations of domination are far more complex and historically contingent than most analyses of industry and "the auto worker" have suggested.